Character Building Of Adolescents Based On The Al-Qur'an And Hadith In Preventing Drug Abuse Factors - syarniah, syarniah; Barni, Mahyuddin; ZA, Ali Muammar; Hermina, Dina; Huda, Nuril (JURNAL CITRA KEPERAWATAN, 2024)
Narcotics, psychotropic substances, and addictive substances are substances that can provide a calm, or excited effect on its users, but also provide negative effects such as hallucinations, loss of emotional and behavioral control. Drug abuse has spread to various age groups from school age to adults. It is necessary to build the character of adolescent behavior based on the Al-Qur'an and Hadith to prevent drug abuse. The purpose of the study was to analyze the character building of adolescents based on the Al-Qur'an and Hadith in dealing with drug abuse factors. The study population was adolescents aged 12-19 years, the sample size was 95 respondents. Questionnaire research instrument. Correlational survey research method with cross sectional approach. Data analysis using Spearman rank test. The results of the study found substance factors that affect the risk of drug abuse low category as much as 92.6% and high category as much as 7.4%. The risk of drug abuse was found to be 94% of non-users and 6% of drug users. There is a perfect relationship between substance factors and the risk of drug abuse in adolescents, ρ = 0.000; α, r = 0.920. The Al-Qur'an and Hadith provide moral guidance that prohibits drug use as part of adolescent character to prevent drug abuse. It is necessary to strengthen the character based on the Al-Qur'an and Hadith in adolescents to prevent drug abuse behavior.